Effect of Alkaloid Compound 3,6,7-trimethoxy-4-methyl-1,2,3,4- tetrahydro-isoquinoline of Swietenia macrophylla King Seed on Lipid Profile and Liver Tissue RBP4 Expression on Type 2-diabetes Rats - Prasetyastuti; Setiawan, Singgih; Ardelia, Yuwinda Prima; Hanifah, Tsurayya Fatma; Singgo, Yunardi; Sunarti (Pakistan Journal of Nutrition, 2016)
Background: Retinol Binding Protein 4 (RBP4) is adipocytokine that it’s secretion and expression in adipose tissue is highly correlated with glucose uptake and insulin sensitivity. Increasing of RBP4 in type 2-diabetes mellitus correlate with insulin resistence. Swietenia macrophylla king contain alkaloid, saponin and flavonoid. Objective: The aim of this study is to investigate the effect of 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline alkaloid compound of Swietenia macrophylla king seed to lipid profile and liver tissue RBP4 expression in type 2-diabetes rats. Methodology: Twenty five adult rattus norvegicus were used, five in each group. Group I: Diabetic rat (untreated), group II: Diabetic rat receive glibenclamid, group III: Diabetic rat receive 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline dose 10 mg/200 g b.wt., day–1, group IV: Diabetic rat receive 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline dose 20 mg/200 g b.wt., day–1 and group V: Diabetic rat receive 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline dose 40 mg/200 g b.wt., day–1. Blood samples were analysed for blood glucose, cholesterol, low density lipoprotein, triglyceride and high density lipoprotein level before and after 4 weeks treatment. At the end of the experiment sample of liver tissue were removed for immunohistochemical analysis. Results: Blood glucose level decreased significantly (p<0.05) in group II, III, IV and V. Cholesterol level decreased non-significantly (p>0.05), Low Density Lipoprotein (LDL) decreased significantly (p<0.05) at dose 40 mg/200 g b.wt. High Density Lipoprotein (HDL) level increased significantly (p<0.05) at doses 10 and 20 mg/200 g b.wt. Conclusion: However, the expression of Retinol Binding Protein 4 (RBP4) decreased after treatment with 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline. These results demonstrated that 3,6,7-trimethoxy-4-methyl-1,2,3,4-tetrahydro-isoquinoline increased HDL and decreased LDL and RBP4 expression.